Fiscal and monetary stabilization policy at the zero lower bound: Consequences of limited foresight - Michael Woodford; Yinxi Xie (Bank of Canada, 2021)
This paper reconsiders the degree to which macroeconomic stabilization is possible when the zero lower bound is a relevant constraint on the effectiveness of conventional monetary policy, under an assumption of bounded rationality. In particular, we reconsider the potential role of countercyclical fiscal transfers as a tool of stabilization policy. Because Ricardian equivalence no longer holds when planning horizons are finite (even when relatively long), we find that fiscal transfers can be a powerful tool to reduce the contractionary impact of an increased financial wedge during a crisis and can even make possible complete stabilization of both aggregate output and inflation under certain circumstances, despite the binding lower bound on interest rates. However, the power of such policies depends on the degree of monetary policy accommodation. We also show that a higher level of welfare is generally possible if both monetary and fiscal authorities commit themselves to history-dependent policies in the period after the financial disturbance that causes the lower bound to bind has dissipated.
Keywords: E52; E63; E7; 330; Monetary policy; Fiscal policy; Central bank research; Business fluctuations and cycles